The contribution of volunteer recorders to our understanding of biological invasions. (23rd March 2015) - Roy, Helen E.; Rorke, Steph L.; Beckmann, Björn; Booy, Olaf; Botham, Marc S.; Brown, Peter M. J.; Harrower, Colin; Noble, David; Sewell, Jack; Walker, Kevin
<x xml:space="preserve">Abstract</x> The process of invasion and the desire to predict the invasiveness (and associated impacts) of new arrivals has been a focus of attention for ecologists over centuries. The volunteer recording community has made unique and inspiring contributions to our understanding of invasion biology within Britain. Indeed information on non‐native species (NNS) compiled within the GB Non‐Native Species Information Portal (GB‐NNSIP) would not have been possible without the involvement of volunteer experts from across Britain. Here we review examples of ways in which biological records have informed invasion biology. We specifically examine NNS information available within the GB‐NNSIP to describe patterns in the arrival and establishment of NNS providing an overview of habitat associations of NNS in terrestrial, marine and freshwater environments. Monitoring and surveillance of the subset of NNS that are considered to be adversely affecting biodiversity, society or the economy, termed invasive non‐native species (INNS), is critical for early warning and rapid response. Volunteers are major contributors to monitoring and surveillance of INNS and not only provide records from across Britain but also underpin the system of verification necessary to confirm the identification of sightings. Here we describe the so‐called 'alert system' which links volunteer experts with the wider recording community to provide early warning of INNS occurrence. We highlight the need to increase understanding of community and ecosystem‐level effects of invasions and particularly understanding of ecological resilience. Detailed field observations, through biological recording, will provide the spatial, temporal and taxonomic breadth required for such research. The role of the volunteer recording community in contributing to the understanding of invasion biology has been invaluable and it is clear that their expertise and commitment will continue to be so. © 2015 The Linnean Society of London, Biological Journal of the Linnean Society, 2015, ●●, ●●–●●.